Transcriptional regulation of the human alpha 2(I) procollagen gene - Leaner, Virna Drucille (Division of Medical Biochemistry and Structural Biology, 2018)
The objective of this study was to investigate the cell- and species-specific regulation of the α2(1) pro collagen gene by analysing trans-acting factor interactions within the proximal promoter of the gene and to identify the genes coding for these trans-acting factors. α2(1) procollagen gene expression was examined in a number of diff erentiate<;l cell lines and shown to differ significantly between normal fibroblasts (WI-38, FG₀), transformed fibroblasts (CT-1, SVWI-38), HT1080 fibrosarcoma, HepG2 hepatocellular carcinoma, L77 lymphoblasts and breast cancer epithelial cells (MDA-MB-231, ZR-75-2). These differences were due to changes in transcription of the α2(1) procollagen gene as shown by Northern blot analysis and nuclear runon transcription experiments . Analysis of DNA-protein interactions with the proximal α2(1) procollagen promoter showed the presence of at least two DNA-protein complexes (complexes I and III) in collagen producing cell lines, while cells where collagen synthesis did not occur contained a third DNA-protein complex (complex II). α2(1) procollagen gene expression was therefore shown to be associated with the presence of complexes I and III while repression of the gene was associated with the presence of complexes I and II and the partial or complete absence of complex III. Complex I is a ubiquitous factor which binds the inverted CCAAT box located between -92 and -80 (G/CBE) with an apparent Kd of 2.9nM. Complexes II and III both bind an adjacent DNA sequence between -78 and -67 (the CME) with Kd values of 4.2 and 3.5nM respectively. While the CCAA T boxes in the human and mouse promoters are identical, a 3bp mismatch was detected in the CME. This mismatch abolished the formation of complex II and III on the mouse promoter, even though mouse cells contained complex II proteins. The difference in the CME binding site between rodent and human promoters implied species-specific regulation of the α2(1) procollagen gene. Transfection of human and mouse proximal α2(1) procollagen promoter/CAT constructs into human cells (CT-1) indicated that the human promoter had higher activity than the mouse promoter, whilst the two promoters had equivalent activities in rodent cells. These promoter activities may be accounted for by the differences in trans-acting factor binding to the two promoters. Complex I formation was competed out by the mouse CBF and NF-Y consensus oligonucleotides, while the mouse anti-CBF-B antibody resulted in a supershifted complex I. These results indicate that complex I is a member of the heterologous CCAAT-binding proteins and possibly related to or similar to the mouse CBF. The treatment of nuclear extracts with calf intestinal phosphatase resulted in a loss of complex I formation on the human and CBF binding to the mouse promoters. The Ser/Thr phosphatase, PP2A, specifically inhibited complexes II and ill formation. Nuclear extracts from CT-1 and U937 cell lines treated with the kinase inhibitor, staurosporin, was accompanied by a loss in DNA-protein interaction. This inhibition of DNA-binding activity was not observed using the tyrosine kinase inhibitor, genistein, and the PP2A phosphatase inhibitor, okadaic acid. Staurosporin also had a significant inhibitory effect on α2(1) procollagen promoter activity in CT-1 cells transfected with the human proximal α2(1) procollagen promoter and on steady state collagen mRNA levels. These results indicate that phosphorylation is required for the binding of trans-acting factors to the proximal α2(1) procollagen promoter and in transcriptional regulation of this gene. In support of the suggestion that phosphorylation events play a role in transcriptional regulation of the α2(1) procollagen gene, CT-1 cells treated with the protein kinase C activator, PMA, showed a significant reduction in α2(1) procollagen mRNA levels. A lambda gt11 expression library was screened to obtain cDNA's encoding proteins that bind the CME in the human α2(1) proximal promoter. A cDNA clone of 958 bp with a predicted open reading frame of 116 amino acids (12.5kD) was obtained. No significant DNA or polypeptide sequence homologies existed in the databank, indicating the possibility of a novel trans-acting factor. Binding of this fusion protein was specific for the CME as observed in South Western blotting and gel shift assays using competitor DNA sequences. Northern blot analysis detected a mRNA transcript of approximately 4kb predominantly in cells where α2(1) procollagen expression is repressed.